Technology Transfer and Good Manufacturing Practices for Robusta Coffee as a Leading Product of Educational Tourism in Wonodadi Village, Buayan District - Maksum, Ali; Purbowati, Ike Sitoresmi Mulyo; Wijonarko, Gunawan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Forest Farmer Group/ Kelompok Tani Hutan (KTH) Tani Jaya located at RT 03 RW02 Blok Blanakan, Wonodadi Village, Buayan District, Kebumen Regency, Central Java. This KTH manages a coffee plantation with Robusta coffee under a pine forest of 7 hectares. Currently, the coffee production of KTH Tani Jaya is 1000 kg/year and is sold exclusively to the local market in Kebumen Regency. The coffee products of KTH Tani Jaya currently do not meet the quality and food safety standards. The products produced are often inconsistent, for example, the roasting results are sometimes too burnt. The solution that can be used is the implementation of Good Manufacturing Practices (GMP). The method used is training and guidance through pre and post-tests. The results of the pre-test showed that the knowledge and basic knowledge of farmers about GMP was still limited, with a low average score in the areas of raw material control and documentation. After intensive training and guidance, the post-test results showed that participants had a significantly improved understanding of GMP, especially with regard to the control and documentation of raw materials.